2022
DOI: 10.1186/s40364-022-00410-3
|View full text |Cite
|
Sign up to set email alerts
|

Physio-pathological effects of N6-methyladenosine and its therapeutic implications in leukemia

Abstract: N6-methyladenosine (m6A), the most prevalent epigenetic modification of RNA in mammals, has become a hot topic throughout recent years. m6A is involved with every links of the RNA fate, including RNA splicing, nuclear export, translation and stability. Due to the reversible and dynamic regulatory network composed of ‘writers’ (methylase), ‘erasers’ (demethylase) and ‘readers’ (m6A binding proteins), m6A has been deemed as an essential modulator in vast physiological and pathological processes. Previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…Using these inhibitors, researchers inhibited the proliferation of a panel of AML cell lines and primary AML leukaemia stem cells in patient-derived xenotransplantation mice. Therefore, FTO and its analogues may be effective molecular targets for inhibiting leukaemogenesis in leukaemia stem cells [161][162][163]. Previous studies also indicated that YTHDF1 was strongly associated with a poor prognosis for ovarian cancer, breast cancer, and other female reproductive disorders [132,164,165].…”
Section: A Rna Methylation Sheds Light On the Diagnosis And Treatment...mentioning
confidence: 99%
“…Using these inhibitors, researchers inhibited the proliferation of a panel of AML cell lines and primary AML leukaemia stem cells in patient-derived xenotransplantation mice. Therefore, FTO and its analogues may be effective molecular targets for inhibiting leukaemogenesis in leukaemia stem cells [161][162][163]. Previous studies also indicated that YTHDF1 was strongly associated with a poor prognosis for ovarian cancer, breast cancer, and other female reproductive disorders [132,164,165].…”
Section: A Rna Methylation Sheds Light On the Diagnosis And Treatment...mentioning
confidence: 99%
“…As the most abundant chemical modification in eukaryotic mRNAs, N 6 -methyladenosine (m 6 A) plays a crucial role in the initiation, progression, and drug resistance of human cancer [8][9][10][11][12]. Several studies have indicated that alterations in m 6 A modifications contribute to leukemia development: m 6 A writers (i.e., methyltransferase-like 3 (METTL3) [13,14], methyltransferase-like 14 (METTL14) [15,16] and Wilms' tumor 1-associating protein (WTAP) [17]), erasers (i.e., fat mass and obesityassociated protein (FTO) [18,19] and α-ketoglutaratedependent dioxygenase AlkB homolog 5 (ALKBH5) [20,21]), and readers (i.e., YTH domain family 2 (YTHDF2) [22,23]) are found to act as oncogenes in AML.…”
Section: Introductionmentioning
confidence: 99%